Pellets de biochar como condicionador de solo na produção e nutrição de Urochloa brizantha cv. BRS Paiaguás - José Mendes dos Santos Júnior (2022)
The use of biochars in sustainable food production can be considered an alternative of management for conditioning the chemical and physical properties of the soil and the use of organic residues. However its use in agriculture is still controversial, due to the amounts to be applied and because the small size of the particles, which can cause respiratory problems when inhaled. Such inconveniences can be alleviated by means of pelletizing and enriching the biochar with mineral fertilizers. The objective was to evaluate the effects of the application of bovine manure biochar (BEB) on the chemical properties of the soil and on the growth of Urochloa brizantha cv. BRS Paiaguás grass. The biochar was produced from the pyrolysis of bovine manure at 450 °C. After chemical and physical characterization, it was held the biochar pelletizing with and without potassium phosphate (PK) fertilizer, using cassava starch as a binder, in a 2:2:1 ratio (biochar:PK:binder) and 4:1 (biochar:binder). The mixtures were introduced into a mold with holes and dried at 65 °C for pellet formation. An experiment, in pots in a greenhouse, was carried out for the agronomic evaluation of the organomineral fertilizer for five cropping cycles (cuts) of the grass, in a 2x2x2+1 factorial arrangement, in a completely randomized design, with five replications. The treatments consisted of the use of non-pelleted and pelleted biochar, without and with the application of soil acidity corrector, without and with PK in the pellet, in addition to an additional treatment consisting of the natural soil. In the PK treatments, 200 mg dm-3 of P and 250 mg dm-3 of K were added. In each cycle, the aerial part dry biomass (BSPA) and the accumulation of macro and micronutrients of the grass were evaluated. After the cultivation period, root dry biomass (BSRA) was determined, in addition to soil chemical analysis. In the soil, the application of biochar without and with pelleting, with liming, regardless of fertilization, raised the pH to values close to 7,0. The highest levels of Ca and Mg were obtained in treatments with liming, while the highest levels of P and K were observed in treatments with pelleted biochar and enriched with these nutrients. In the first cycle, BSPA was 18,28% higher in the treatment with non-pelletized biochar and PK fertilization. From the second cycle onwards, the highest productions of BSPA were obtained in treatments with pelleted biochar and enriched with PK. The BSPA in the control treatment presented significantly lower, in relation to the other treatments, in all cultivation cycles. BSRA showed significantly lower in the control treatment than in the other treatments. The highest foliar accumulations of macronutrients were obtained in treatments with liming and PK fertilization, while, for micronutrients, the highest averages were observed in treatments with PK application. Therefore, BEB increased soil fertility and contributed to the growth of U. brizantha cv. BRS Paiaguás, being the highest productions obtained in treatments with pelleted biochar and enriched with PK.